Avaliação de pastos de capim elefante em sistemas forrageiros de produção convencional e orgânica sob pastejo - Seibt, Daiane Cristine (2019)
Elephant grass has great importance in regions of tropical and subtropical climate, especially in dairy farms. Normally, this forage is established in monoculture under conventional production, using high levels of nitrogen fertilization. The establishment in mixture with other species, combined with the use of organic fertilizers can be characterized as a more sustainable production strategy. Under these conditions, few studies were developed, either under conventional production or under organic production. The present work involves two studies in which the objective was to evaluate the productivity, nutritive value and growth dynamics of elephantgrass leaves and tillers in pastures submitted to conventional and organic production systems under grazing conditions. In the first study, with meta-analysis, we used data from 20 experiments, adding 354 observations, of elephantgrass pastures under grazing conditions between 2002 and 2016. The treatments consisted of five forage production systems, four under conventional production (1-4) and one under organic production (5): 1) elephant grass in monoculture + chemical fertilizer; 2) elephant grass in mixture with other grasses + chemical fertilizer; 3) elephant grass in mixture with other grasses + forage peanut + chemical fertilizer; 4) elephant grass in mixture with other grasses + clover + chemical fertilizer; 5) elephant grass in mixture with other grasses + organic fertilizer. In the second study, which evaluated the morphogenic characteristics of elephantgrass, the experiment was conducted between September 2015 and May 2017. The treatments consisted of three forage production systems, two under conventional production (1-2) and one under organic production (3): 1) elephant grass in monoculture + chemical fertilizer; 2) elephant grass in mixture with other grasses + chemical fertilizer; 3) elephant grass in mixture with other grasses + organic fertilizer. For this study, the experimental design was a completely randomized, with three treatments, three replications, with repeated measures in time. For the productive variables of the pasture, biomass of leaf blades and forage accumulation rate, the highest results were obtained in the monoculture system, especially in the summer. On the other hand, for crude protein content, higher values were observed in systems with forage mixtures under organic production and consortium with legumes. For the morphogenic characteristics no differences were observed between conventional production systems in monoculture and organic production. However, there was a seasonal pattern of variation in morphogenic responses and structural composition of elephantgrass characterized by higher growth rates and proportion of leaf blades in the spring, decreasing with the advancement of the production cycle, in summer through fall. However, there was an inverse behavior with increase of tillering rate and leaf senescence reduction, indicating maintenance of elephant grass productivity at the end of the summer period. It is concluded that the systems in with forage mixtures, under conventional or organic production, presented productivity equivalent to the monoculture system under conventional production.